Impact of water supply on stomatal conductance, light use efficiency and growth of tropical Eucalyptus plantation in Brazil - Otto, Marina Shinkai Gentil; Vergani, Aline Regina; Gonçalves, Antônio Natal; Silva, Sérgio Ricardo; Vrechi, Arthur; Stape, José Luiz (Revista Ecologia e Nutrição Florestal - ENFLO, 2017)
Eucalyptus plantations of Brazil are expanding to areas subjected to water stress, and the water stress is considered a main environmental factor that limit growth and productivity of plantations, this occurrence implies the necessity for advance knowledge about physiological processes of Eucalyptus under different conditions of water availability. In this study, leaf gas exchange and light use efficiency of Eucalyptus under tropical field conditions in Brazil was evaluated to assess the effect of water supply on wood production. The experiment was performed in Eunápolis, Bahia, Brazil (16°22’40’’S, 39°34’48’’W) and we evaluated two treatments (irrigated and rainfed) of Eucalyptus forest clonal plantation on second rotation, established in August 2009. Leaf gas-exchange parameters were analyzed in 15-month plants using a Portable Photosynthesis System LI-6400xt and to calculate the light use efficiency, the vegetation area index (VAI) were measured through hemispherical photos using a camera - model Cyber shot ® Digital Camera Sony DSC - F828 coupled with a Fisheye Lens Opteka 0.22X AF ®. Irrigated trees showed higher biomass increment as a result of higher light use efficiency and lower absorbed photosynthetically active radiation, less carbon allocation to the below-ground; and lower stomatal conductance in relation to vapor pressure deficit (VPD) variation. These results showed that Eucalyptus species are responsive to water supply, and the reduction of stomatal conductance in relation to the VPD variation explains the higher stem biomass increase and greater LUE in the irrigated treatment.